2022
DOI: 10.3389/fphys.2021.753034
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals Changes in the Intestinal Microbiome, Transcriptome, and Methylome in a Rat Model of Chronic Non-bacterial Prostatitis: Indications for the Existence of the Gut-Prostate Axis

Abstract: Chronic non-bacterial prostatitis (CNP) is one of the most prevalent diseases in human males worldwide. In 2005, the prostate-gut axis was first proposed to indicate the close relationship between the prostate and the intestine. This study investigated CNP-induced changes of the gut microbiota, gene expression and DNA methylation in a rat model by using multi-omics analysis. Firstly, 16S rDNA sequencing presented an altered structure of the microbiota in cecum of CNP rats. Then, transcriptomic analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Further probing revealed that EAP mice have obviously decreased contents of SCFA propionate in both feces and serum, and propionic acid supplementation attenuated EAP severity and restored its Th17/Treg balance, which was possibly linked to the GPR43 activation and HDAC6 inhibition. Our research broadens the horizons of the correlation between gut microflora and extra-intestinal organs or immune cells and provided new lines of evidence for the previously proposed concept of the “gut–prostate” axis ( 33 ).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Further probing revealed that EAP mice have obviously decreased contents of SCFA propionate in both feces and serum, and propionic acid supplementation attenuated EAP severity and restored its Th17/Treg balance, which was possibly linked to the GPR43 activation and HDAC6 inhibition. Our research broadens the horizons of the correlation between gut microflora and extra-intestinal organs or immune cells and provided new lines of evidence for the previously proposed concept of the “gut–prostate” axis ( 33 ).…”
Section: Discussionsupporting
confidence: 51%
“…Further probing revealed that EAP mice have obviously decreased contents of SCFA propionate in both feces and serum, and propionic acid supplementation attenuated EAP severity and restored its Th17/Treg balance, which was possibly linked to the GPR43 activation and HDAC6 inhibition. Our research broadens the horizons of the correlation between gut microflora and extra-intestinal organs or immune cells and provided new lines of evidence for the previously proposed concept of the "gut-prostate" axis (33). It has been now becoming widely accepted that the large amounts of commensal gut bacteria not only are restricted to regulate the intestinal mucosal immunity and maintain the intestinal homeostasis, but also exert systemic effects on immune cells in extra-intestinal organs or tissues (34).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Antibiotics may cause a change in bacterial diversity that leads to dysbiosis [21,22]. In this regard, recent research has established a "gutprostate axis" in the association between gut microbiota and prostate health, including prostate cancer [23][24][25]. Insulin-like growth factor 1 (IGF-1), affected by the gut microbiome, has been linked to prostate cancer, which acts as an aggravating factor [24].…”
Section: Discussionmentioning
confidence: 99%
“…51 Noteworthy, currently available conventional analgesics (such as acetaminophen, nonsteroidal anti-inflammatory drugs, and opioids) and even other, more evidence-based pharmacological options (including anti-spasmodics, tricyclic antidepressants, and other neuromodulatory therapies), are frequently ineffective and/or associated with significant side effects for patients with interstitial cystitis, CNP, and IBS, thus are difficult to treat. 42,52 Potentially, one of such could be represented by microbiome modification. Until recently, it was believed that human urogenital tract is sterile.…”
Section: Anatomical Peculiarities Of Pelvic Region and Cross-organ Se...mentioning
confidence: 99%